Hubungan Pengoptimalisasian Teknologi Digital Terhadap Minat Belajar Bahasa Indonesia di Kalangan Siswa Sekolah Dasar - Tiara Indrajava Puspita; Tiara Novianti; Adrias Adrias; Salmaini Safitri Syam (Jurnal Bintang Pendidikan Indonesia, 2025)
The purpose of this study was to examine the relationship between elementary school students' interest in learning Indonesian and the use of digital technology. Given that technology has become an important part of the educational process, it is expected that students' motivation and interest in learning will increase in the contemporary digital era. Data for this study were collected using survey methodology and quantitative approaches. 20 randomly selected elementary school students were given questionnaires. With a p value <0.05, the results of the data analysis showed a substantial positive relationship between interest in learning Indonesian and the use of digital technology in the classroom. The study showed that students were more interested in learning Indonesian when digital technology was used optimally. It is hoped that this study will help educators and policy makers to better integrate digital technology into the classroom learning process in order to increase student engagement and academic achievement.